The Renaissance restored : paintings conservation and the birth of modern art history in nineteenth-century Europe - Hayes, Matthew, 1977- (Getty Conservation Institute, 2021)
"This volume charts the intersections between art history and conservation in the treatment of Italian Renaissance paintings in nineteenth-century Europe"--